2013
DOI: 10.1080/19768354.2013.782897
|View full text |Cite
|
Sign up to set email alerts
|

Differential response to abiotic conditions, predation risk, and competition determine breeding site selection by two anuran species

Abstract: Sympatry of species has been a central debate in ecology for decades but the mechanisms that allow coexistence are still heatedly disputed. The main paradigms include the importance of abiotic conditions, predation risk, and competition as determinants of community structure. In this study, we investigated oviposition-site selection of two anuran species, Asiatic toads (Bufo gargarizans) and dark-spotted frogs (Pelophylax nigromaculata), which coexist in southwestern China. We sampled the abiotic and biotic at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Therefore, environmental factors, such as the low humidity in the post‐rainy season, cannot be excluded from the influences capable of shaping sperm morphology (Pucci et al, 2020; Zeng et al, 2014). Many studies have reported reproductive responses in anuran species related to the environment, such as spermatogenesis influenced by temperature and humidity (Chaves, Moura, et al, 2017; Rastogi, 1976), the selection of breeding sites based on abiotic conditions (Yu & Guo, 2013), and species from different fertilization environments presenting unique sperm morphology (Pucci et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, environmental factors, such as the low humidity in the post‐rainy season, cannot be excluded from the influences capable of shaping sperm morphology (Pucci et al, 2020; Zeng et al, 2014). Many studies have reported reproductive responses in anuran species related to the environment, such as spermatogenesis influenced by temperature and humidity (Chaves, Moura, et al, 2017; Rastogi, 1976), the selection of breeding sites based on abiotic conditions (Yu & Guo, 2013), and species from different fertilization environments presenting unique sperm morphology (Pucci et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Amphibian species, however, rely on different mechanisms to cope with aquatic environments and show varying degrees of tolerance (Hopkins and Brodie Jr. 2015), with variables, such as water chemistry (Viertel 1999), dissolved oxygen (Yu and Guo 2013), total dissolved solids (Browne et al 2009) and water temperature (Indermaur et al 2010), having different impacts on species. For instance, some species have a greater osmotic tolerance to brackish habitats (Wu et al 2014), with larvae of species, such as Bufotes viridis, found in brackish water bodies with salinity up to 25 ppt (Katz 1973).…”
Section: Introductionmentioning
confidence: 99%